Explicitly correlated study of the torsional vibrations of HSOSH molecule. Comparison with MP2/CBS(T, Q) level of theory. Issue 1 (12th December 2022) - Pitsevich, G.; Malevich, A.; Doroshenko, I.
Abstract: Geometric parameters of equilibrium configurations of trans- and cis-conformers of HSOSH molecule, their dipole moments, rotational constants in the ground electronic and vibrational states, and kinetic parameters corresponding to two torsional coordinates γ 1 and γ 2 were calculated at CCSD(T)-F12/cc-pVDZ-F12 level of theory. In the latter case, at each node of the two-dimensional grid γ 1 and γ 2 all other geometric parameters of the molecule were optimized. The obtained configurations were used for calculation of 2D potential energy surface at CCSD(T)-F12/cc-pVTZ-F12 level without additional optimization. The energies of a number of excited torsional states were determined by numerically solving the vibrational Schrödinger equation of restricted dimensionality using two-dimensional complex Fourier series. The obtained data on the frequencies of torsional vibrations of S-H groups in the two conformers and the frequencies of tunneling in the ground and excited torsional states are compared with the results obtained earlier at MP2/CBS(T, Q) level of theory.